(untitled) (Metallurgy and Foundry Engineering, 2016)
This paper discusses the possibility of assessing the quality of materials in terms of their mechanical properties as determined by a modified low-cycle fatigue test applied in these studies. The developed computer program adapted to the needs of an MTS universal testing machine is described, as are the details of an algorithm used by this program. The compatibility of test results obtained by the two methods (i.e., the standard low-cycle fatigue test [LCF] and its modified original version [MLCF]) has been demonstrated on the samples of selected non-ferrous metals alloys.